Implementasi Metode Single Moving Average Untuk Prediksi Stok Produsen - Duanna Purnamasari; Endah Ratna Arumi; Ardhin Primadewi (JURIKOM (Jurnal Riset Komputer), 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the national economy such as MSMEs as small-scale food producers. MSMEs as small-scale food producers in the Magelang area are quite diverse, especially in the Deyangan area. To know the amount of daily stock. Keripik "Ngangeni" manually applies the amount of production according to production capabilities based on the number of materials or the number of employees who come. This has caused the company experience shortages of stock several times at the request of buyers. Single Moving Average (SMA) as a method for predicting producer stocks which has advantages in calculating averages and does not require weighting. SMA accuracy is assessed by forecasting accuracy tests, namely Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). This study uses data from July 2021 to April 2022. The results of SMA forecasting using 8 periods in March and April both produce a value of 74 kg. Forecasting with 8 periods is the best forecast because it has a small forecasting accuracy value of 0.5 for MAD and 4 for MAPE